Human rights issues in Vietnam – The United States of America relations - Cường Nguyễn Anh (Cogent Social Sciences)
The issue of human rights is a constant concern in U.S. policy towards Vietnam. It has always been the main factor in implementing U.S. foreign policy with Vietnam and other countries in general. To normalize relations with the U.S. Vietnam has actively returned the remains of Americans missing in the war without preconditions, but human rights in U.S. foreign policy are not simple. That is a long process to understand and comply with the human rights requirements of the United States. Although cooperation and struggle in relations between Vietnam and the U.S. going on since the early days of normalization, the difference in awareness of human rights has narrowed. Why these good results? Can the U.S. and Vietnam make new strides in relations? How can differences in perceptions of human rights be resolved? Based on the judgment of scholars and by analyzing the historical activities of the relationship between the two countries, the article is to give crucial suggestions to note in making foreign policy of each country.